Case Study: Implementation of Health Education on Clean and Healthy Living Behavior (PHBS) in Families with Toddlers Suffering from Diarrhea - Pipit Wiliyanarti; Muhammad Rauf Elvandi; Yuanita Wulandari (KHD Production, 2024)
Clean and healthy living behavior is crucial for family health, with families, especially mothers, playing a key role in implementing Clean and Healthy Living Behavior (CHLB) to impact overall family health. This study aims to evaluate the application of CHLB in families with toddlers who have experienced diarrhea and to assess their knowledge following health education. Methode: This descriptive study used a case study approach, focusing on families with toddlers who had diarrhea in Dukuh Sutorejo RT.01 RW.06, Surabaya. The study utilized a closed-ended questionnaire with 30 questions, involving 2 families: one with an extended family type and one with a nuclear family type. The findings revealed that the CHLB application in Family A (Extended Family) scored 44 (Satisfactory), while Family B (Nuclear Family) scored 40 (Insufficient), indicating that neither family met the CHLB standards. However, knowledge improved significantly after health education, with an average score of 77.5, indicating a good understanding. The study identified differences in CHLB implementation between extended and nuclear families, with extended families showing better application. Health education effectively enhanced family knowledge about the importance of CHLB in preventing diarrhea. There is a notable disparity in CHLB application between extended and nuclear families, with extended families demonstrating better practices. Health education significantly improved families' knowledge, emphasizing the need for increased awareness and adherence to CHLB to prevent toddler diarrhea.